Development of a module to address interest and anxiety in learning science for female secondary pupils in Nigeria / Tukur Muhammad - Tukur , Muhammad (2020)
The purpose of this study was to develop a Module for female secondary pupils to help increase interest and anxiety (FSSMIA) in learning science at a selected public day senior secondary school in Zamfara, Nigeria. The study further intended to create awareness for parents to perceive the importance of their daughters learning science. A Type 1 Developmental Research Design was used in the study based on the ADDIE Model. First, a needs analysis with selected female pupils was conducted through a focus group interview. Analysis of related curriculum documents and textbooks was also done to establish the need for this study. Second, Gagne’s nine events instructional approach was adopted in designing the delivery of the lessons in the module. Two rounds of consensus by experts in the field of science education were obtained to design the elements, content, and framework of the module. Third, the development of the module (FSSMIA) was finalised after a workshop with a group of selected science teachers and parents together with officers from the Ministry of Education according to the design that was agreed upon. Fourth, six lessons from the module and five home projects were executed. Fifth, the impact of the module on the teacher, female pupils, and parents was evaluated through data collection techniques such as interviews, videos and observations field notes. Overall, there were two phases to the study. The first phase was the execution of the six lessons in the module by a selected female teacher. The second phase was conducting the home projects using local materials with the involvement of the parents. In-depth thematic qualitative analysis revealed that the module influenced the teacher by improving her confidence level and assisted her to be more effective in teaching. It was found that the module also helped the pupils to be less anxious in learning science as they were fully engaged in the learning process through role-play activities. The female pupils also felt increased interest because the lessons are linked with elements related to daily life infused in the module. The home projects helped the parents perceive the importance of science, which stimulated them to change their attitudes about their daughters learning science at the higher secondary and tertiary levels for their future careers. The above positive findings from using FSSMIA could be due to the involvement of parents in the home projects, the role play activities in class, and four main elements that distinguish the present study’s module FSSMIA from other modules, which contributes to existing literature. The four elements included in the module are (i) stories and achievements of women scientists, (ii) religious beliefs, (iii) cultural activities, and (iv) everyday health. The study has significant implication for embedding elements of culture and religion in science curriculum development and science teacher education, and parents’ perspectives of female pupils learning science in Nigeria.